Local Photovoltaic Properties of Graphene–Silicon Heterojunctions (Phys. Status Solidi B 12/2018). Issue 12 (13th December 2018) - Rahova, Jaroslava; Sampathkumar, Krishna; Vetushka, Aliaksei; Ledinsky, Martin; Hajkova, Zdenka; Fejfar, Antonin; Frank, Otakar
Abstract : The rise of nanomaterials requires a day‐to‐day implementation of suitable nanoscale characterization techniques. Atomic force microscopy (AFM) has become such a one, capable of providing diverse information about the sample topography, mechanical and electrical properties with resolution down to few nanometers. The work by Otakar Frank and co‐workers (article no.1800305 ) shows two examples of AFM application to describe local photovoltaic properties of graphene–silicon Schottky junctions. Direct measurement of I–V curves at selected points has been employed to discriminate the effect of increased p‐doping of the graphene layer. Scanning the samples in the contact mode, followed by reconstruction of I–V curves, has been utilized to evaluate the separation between the graphene layers and/or the substrate. It is imperative to stress that the standard red diode used in the deflection‐type AFM provides more than enough light to generate the photocurrent, hence a great attention has to be paid whenever conductive AFM is used for the characterization of photo‐active materials.